Carbon balance and net ecosystem production in Quercus glauca forest, Jeju Island in South Korea - Jeong, Heon Mo; You, Young Han; Hong, Seungbum (Journal of Ecology and Environment, 2022)
Background: To assess the carbon sequestration capacity and net ecosystem productivity (NEP) of Quercus glauca forests, we analyzed the net primary productivity (NPP), carbon storage, and carbon emission of soil in a Q. glauca forest on Jeju Island (South Korea) from 2016 to 2018. Results: The average carbon stock in the above- and below-ground plant biomass was 223.7 Mg C ha–1, while the average amount of organic carbon fixed by photosynthesis was 9.8 Mg C ha–1 yr–1, and the average NPP was 9.6 Mg C ha–1 yr–1. Stems and branches contributed to the majority of the above- and below-ground standing biomass and NPP. The average heterotrophic carbon emission from the soil was 8.7 Mg C ha–1 yr–1, while the average NEP was 1.1 Mg C ha–1 yr–1. Although the carbon stock, carbon absorption, and soil respiration values were higher than those reported in other oak forests in the world, the NEP was similar or lower. Conclusions: These results indicator that Q. glauca forests perform the role of a large carbon sink through the CO2 absorption in the plants in terms of carbon balance. And it is judged to be helpful as data for assessment of carbon storage and flux in the forests and mitigation of elevated CO2 in the atmosphere. KCI Citation Count: 0